2022
DOI: 10.1007/s12528-022-09334-1
|View full text |Cite
|
Sign up to set email alerts
|

Flipped classroom: motivational affordances of spherical video-based immersive virtual reality in support of pre-lecture individual learning in pre-service teacher education

Abstract: Flipped classroom (FC) is a “blended” instructional approach that requires students to complete pre-lecture individual learning tasks in preparation for participating in related in-lecture peer learning activities. One of the critical problems of FC has been students’ lack of motivation to complete the assigned online pre-lecture tasks prior to attending the corresponding face-to-face lectures. Spherical video-based immersive virtual reality (SV-IVR), which can be produced without costly computing equipment an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 58 publications
2
12
0
1
Order By: Relevance
“…Of them, most studies examined teachers' self‐efficacy after experiencing XR technologies ( n = 7) (e.g., Bautista & Boone, 2015; Gundel et al, 2019; Nissim & Weissblueth, 2017; Pendergast et al, 2022). Several studies also examined the effect of class size on teachers' physiological and psychological stress reactions (Huang et al, 2023b), motivational affordance (Jong, 2023), affective state (Xie et al, 2022), emotional and mood states (Stavroulia et al, 2019), and the effect of the shot size on the psychical distance between virtual characters and their viewers (Kim et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Of them, most studies examined teachers' self‐efficacy after experiencing XR technologies ( n = 7) (e.g., Bautista & Boone, 2015; Gundel et al, 2019; Nissim & Weissblueth, 2017; Pendergast et al, 2022). Several studies also examined the effect of class size on teachers' physiological and psychological stress reactions (Huang et al, 2023b), motivational affordance (Jong, 2023), affective state (Xie et al, 2022), emotional and mood states (Stavroulia et al, 2019), and the effect of the shot size on the psychical distance between virtual characters and their viewers (Kim et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…Several studies recruited a sample with a range of 101–150 ( n = 7). Only two studies have a sample range of 151–200 (Jong, 2023; Nissim & Weissblueth, 2017).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a similar context, according to a systematic review performed by Akçayır and Akçayır, a reverse course leads to positive academic outcomes because it encourages improvement in student learning (e.g., enhanced motivation to learn, positive student attitudes) [26]. Recently, Jong reported that students from teaching subjects of language education, social and humanities education, and mathematics and science education, appreciated flipped courses as having desirable benefits for attention, relevance, and satisfaction, especially in chemistry teaching at the higher education level [27].…”
Section: Discussionmentioning
confidence: 99%
“…During class, students were required to apply their self‐learned knowledge by editing a photograph that they could use together in their group. Jong 16 developed the flipped classroom experience for the “teaching and learning with technology” subject. This is mandatory for students of different degrees before starting the university.…”
Section: Related Workmentioning
confidence: 99%